Pemanfaatan Media Untuk Pembelajaran Ekonomi di Sekolah Menengah Atas - Abd. Ghofur Kuswanto Ety Youhanita (Universitas PGRI Madiun, 2018)
This paper examines the utilization of media in economic learning atsenior high school level in Lamongan Regency which is reviewed from threeindicators, namely a) diffusion of innovation, b) implementation andinstitutionalization, and c) policies and regulations. This study was conductedfor three months from January to March 2018 using a qualitative descriptivedesign using survey method. Technique of collecting data using google formquestionnaire, interview, and study documentation. The subjects of the studywere 22 upper secondary schools selected with purposive sampling methodfrom 218 high schools in Lamongan. The result of the research shows that thereis no diffusion of innovation by high school economics teacher significantly inutilization of media for economic learning. The use of various learning mediautilizes more infrastructure that has been available in schools, eg LCDprojectors and props. Administratively the teacher writes the instructionalmedia used in the Lesson Plans which refer to the Curriculum format 2013, butin practice media usage is adapted to the classroom situation and conditionwhen teaching. In addition, school policies do not provide written regulationsrelating to media utilization standards used by teachers in the learning process.